Mathématiques
Dino95
40

Bonjour pouvez-vous m'aider pour cet exercice. Développer et réduire les expressions suivantes: A= 3(2x+3)+2x(4x-5). B= 3x (x+2) + (x-5)(3x-2). C= (x+3)-[2x-3(4x+2)] D= (x+3)(x+2)(x+4) E= (3x+5)au carré. F= (2x+3)(2x-3)+x(4x-2)

+4
(1) Réponses
rayantebari

A= 3(2x+3)+2x(4x-5) A=6x+9+8x²-10x A=8x²-4x+9 B=3x(x+2)+(x-5)(3x-2) B=3x²+6x+3x²-2x-15x+10 B=6x²-11x+10 C=(x+3)-[2x-3(4x+2)] C=x+3-(2x-12x-6) C=x+3-(-10x-6) C=x+3+10x+6 C=11x+9 D=(x+3)(x+2)(x+4) D=(x²+2x+3x+6)(x+4) D=(x²+5x+6)(x+4) D=x³+4x²+5x²+20x+6x+24 D=x³+9x²+26x+24 E=(3x+5)²=9x²+30x+25 F=(2x+3)(2x-3)+x(4x-2) F=4x²-9+4x²-2x F=8x²-2x-9

Ajouter une réponse